Estrutura do saneamento básico no Brasil: receita, dispêndio de gastos e atenção básica à saúde - Rodrigues, Karla Cristina Tyskowski Teodoro (2020)
The current work interconnects sanitation aspects in a multidirectional form and brings forward different flaws in the field related to costs, service and infrastructure in Brazilian macro-regions that cause a negative impact on the incidence of health-related diseases in Brazil. The subjective is representative in the present national scenario due to clean water and sewage disposal and treatment worldwide access. Besides the fact that this is one of the most important topics in global discussions, in 2020, Brazil has sanctioned law 14.026 as a way to strive for improvement in the field with higher investments in service, infrastructure and legalization of contracts. The urgency in these matters has to do with the fact that great part of the population does not have access to these services and their effects on the environment, development and promotion of human well-being. From this point the view, the current work presents the following research problem: What are the most important factors for the economic raise of companies in the sanitary field? What are the sanitary industry contributions to level up Brazilian people health? Based on this concern, the main objective was to assess the structure of basic sanitation in Brazil through multidimensional analysis of revenue by means of the allocation of expenditures and basic health. The hypothesis suggested that there were improvements in sanitation structure through allocation of service and infrastructure’s revenue, albeit, they were distributed unevenly to all regions from 2007 to 2016. Panel of econometric data and spatial analysis were methodologies used, taking into account data from Sistema Nacional e Informações Sanitárias (SNIS), Instituto Trata Brasil (ITB) e Instituto Brasileiro de Geografia e Estatística (IBGE). The research has shown the fragility of the service systems, engendering bad results to health issues. Apart from that, it did somehow excel in the period, however, there are still loopholes in the stewardship. Spatial data showed an improvement in the reach of water service. Nonetheless, there are still a lot to be done in relation to sewage collection and treatment. In regard to clustes, it has increased the amount of High-High and High-Low clustes. This fact was identified in the Southeast, Midwest and South regions, thus, demonstrating a deficiency in states in the Northeast that have, in their great majority, favorable rates in the coastal area of the states. About North, the region has problems not only in the structure and service, but also lacks in information from its cities and states to the SNIS. In regard to econometric panels, the first is related to financial income from Brazilian cities’ sanitation. Through macro-region analysis, it showed that, in relation to the coverage, regions that had more impact were Midwest and North. In terms of size of population and urbanization, both indicators have risen up, which performance is positive for the financial revenue, mostly because of the Southeast, North and Northeast macro-region. This fact also endorses the principle of economies of scales. As for the table of contents created, which presents emphasis in structure, when the Northern macro-region was evaluated, the variables that presented positive impact on the revenue were extent, consumption and the connections amongst water structure, collection and sewage treatment and exploration to improve basic sanitation. In the Northeast, the variable extension was the one that showed positive feedbacks in regard to the revenue, while the Southeast had good return in production and connections. The South macro-region has a different aspect on account of Paraná state having the best sanitation company in the country. The production and the sewage treatment have stood out for its scope and efficiency. In the Midwest, the variables that had a highlight were related to the extension of the water network, exploration and quantity of water connections, sewage treatment, number of employees and investment. About the econometric panel linked to variables in health, it was possible to confirm that, in the North macro-region, the variable that had a positive impact was disinfection. The extension showed a negative impact in the North, Midwest and Southeast, which implies that the increase in sanitation structure itself it is not enough to provide healthiness development, so other variables are needed, such as improvement in water quality. The service variable showed good aspects in the Northeast and Southeast regions and the wastewater treatment only presented positive impacts for the North. It was possible to verify that this macro-region showed different results comparing to other macro-regions, what may be caused by its unlike structure, which service and sanitation information rates were lower, indicating, therefore, the necessity of in-depth analysis in this macro-region. The analysis of the fourth objective verified that impacts of basic sanitation variables had more influence in some macro-regions, however, what presented the major positive feedback was IFDM’s employment. Conclusion is that, once there is job creation, proportionally, there is income growth and a substantial impact on health due to the possibility of one’s social choice. As a matter of fact, economic issues are interconnected with basic sanitation sector and the challenges in the field are huge. Finally, it is important to highlight that the stewardship aspects are the most relevant ones, directing research, planning and regional data.